ANALISIS USAHA IKAN HIAS AIR TAWAR DI KOTA JAMBI - Ernawati; Suandi; Hadisaputra, Dodi (Program Studi Agribisnis bekerja sama dengan PERHEPI, 2020)
Ornamental fish is a fish that has a distinctive shape, color and character so as to create an aquarium atmosphere that supports spatial layout and is able to provide a peaceful atmosphere. The purpose of this study was to determine the description of ornamental fish business and analyze the feasibility of ornamental fish business in Jambi City. The qualitative method is used to describe descriptively the general description of the location of the study and the characteristics of ornamental fish farmers, while the quantitative method uses the Analysis of Income and Revenue of ornamental fish business, cost analysis, income analysis and cost balance (R/C Ratio), Net Benefits - Cost Ratios (Net B/C), and institutionally descriptive for the betta fish, guppy and botia ornamental fish business. Overall, the general description of ornamental fish farming business in Jambi City is conducted conventionally. The average R/C ratio of the Betta ornamental fish business is 2.60, guppy is 2.02 and botia is 1.22. The highest average NPV in the betta ornamental fish in the mid-scale farming business is Rp. 60,745,160.71, guppy on a large scale is Rp. 31,385,065.48, and botia on a large scale with a value of Rp. 78,034,144.35. Overall, this ornamental fish business has an NPV value of> 0. The ornamental fish business in Jambi City is feasible to run and develop, betta ornamental fish business on a small scale with an average B/C Ratio of 1.15 and medium with an average value of average 1.60, guppy on a small scale with an average value of 1.02, and botia on a medium scale with an average value of 1.00 and large with a value of an average of 1.22. Keywords: Ornamental Fish, Jambi City.